An Analysis of Code Mixing and Code Switching on Cinta Laura’s Video “Kuliah Keluar Negeri Itu Perlu Gak Sih?” - Fresya, Octaviola; Adiantika, Hanif Nurcholish; Susilawati, Susilawati (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
When two or more languages are switched during a monologue or dialog, sociolinguistics who research language used to refer to it as "code-switching" or "code-mixing”. This thesis examines the analysis of code-mixing and code-switching of the Cinta Laura podcast media on Puella's account. This research aims to analyze the types and reasons of code-mixing and code-switching that Cinta Laura uses in the podcast "Kuliah Keluar Negeri itu Perlu Gak sih?".The research method used is a qualitative descriptive method. Data collection techniques used in this research include observation, qualification, and data analysis. The theory used for the types and reasons of code mixing and code switching is Hoffman's (1991) theory.  The results of this research show that the types and reasons of code-mixing and code-switching used by Cinta Laura in the podcast entitled "Kuliah Keluar Negeri itu Perlu Gak sih?" are, the type of code-mixing most dominant is Intra-sentential code-mixing with data results 13 (thirteen), the type of code-switching that is most dominant is Intra-sentential code-switching with data results 7 (seven), and the reason for code-mixing and code-switching that most dominant used is talk about a particular topic with 20 (twenty) data results.